Direct and Indirect Pathways of Variation in Length of Exposure to the Majority Language, Cognitive and Language Skills in Preschoolers' Listening Narrative Comprehension - Raffaele Dicataldo; Maja Roch (MDPI AG, 2021)
Listening narrative comprehension, according to the theoretical framework of the multicomponent model for comprehension, involves numerous skills that interact dynamically between each other and have the potential to give rise to individual differences in comprehension. The purpose of the current work was to define a comprehensive and complete multicomponent model of listening narrative comprehension in preschool age. We investigated how variation in Length of Exposure to majority Language (i.e., how long children have been exposed to the Italian language), lower-order cognitive (WM, inhibitory control, attention shifting), language skills (receptive vocabulary, syntactic knowledge, rapid naming), and higher-order cognitive skills (inferences, TOM, knowledge of story-structure) are related to listening narrative comprehension in Italian of 111 preschool children (Mage = 61 months; SD = 6.8) growing in a monolingual or multilingual context. Structural equation modeling results showed that the model explained 60% variance in listening narrative comprehension in Italian of children aged four to six and predicted the outcome both through direct and mediated paths, coherently with the multicomponent model of comprehension.